Material Flow in Sheet-Bulk Metal Forming - Vierzigmann, Ulrich; Koch, Johannes Peter Karl; Merklein, Marion; Engel, Ulf (Key Engineering Materials, 2012)
The trend towards closely-tolerated complex functional components with an increased functionality shows the limits of classical sheet and bulk metal forming operations. The combination of sheet and bulk metal forming operations to the new process class of sheet-bulk metal (SBMF) operations is a promising approach for producing the requested parts. Combining sheet and bulk metal operations is leading to different surface pressures and hence to different tribological conditions within the forming process. Investigations with FE-simulation have shown, that locally adapted tribological conditions can yield an improvement in material flow and thus, an increased mold filling within SBMF process. As frictional conditions are directly connected to the topography of workpiece and tool, the targeted modification of the workpiece topography can be used to adjust friction values, correspondingly. Within this paper the modification of workpiece topography by abrasive blasting and the resulting influence on the frictional conditions are investigated. Additionally, an approach for the definition of different tribological zones on a SBMF extrusion die is presented.© (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1785)
Keywords: Abrasive blasting; Material flow; Sheet-bulk metal forming; Tribology